DINAMIKA POLITIK BERDESA : STUDI KASUS PILKADES DI DESA SUDIMORO, KECAMATAN SRUMBUNG, KABUPATEN MAGELANG, JAWA TENGAH - Libertus Renaldi (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
This study examines the actors who won the Pilkades contest in Sudimoro Village, Srumbung District, Magelang Regency, Central Java. This research uses qualitative methods by collecting data through observation, documentation, and in-depth interviews with the winning candidates, BPD, the success team, and the community. The results showed that the victory of the actors in the Pilkades contest was motivated by several factors such as many breeds/families, good relations with the community, and support from community leaders and this is the tradition and life habits of the village people. In addition, the practice of money politics or local strongmen is interpreted as a form of negotiation from the community due to the absence of the government in providing public facilities that can be enjoyed by all levels of society.